PEMBANGUNAN PERTANIAN MELALUI PENGUATAN MANAJEMEN USAHA TANI MENINGKATKAN PRODUKSI DAN PENDAPATAN PETANI DESA WALEALE - Yohanes Boni (Mega Aktiva, 2022)
This research was carried out in Wale-ale Village, South Tongkuno District, Muna Regency in 2020. Waleale Village has a wide and fertile farming land, as well as a high farmer work ethic. However, the regional infrastructure is not good and farmers do not have the skills of farming and farming management, so that the production and income of farmers are low which makes it very difficult for farmers to get out of the shackles of poverty. The purpose of this research is to analyze the role of agricultural development in increasing the production and income of farmers in Waleale Village. The research method uses primary data through identification of agricultural resources and problems of increasing production and farmers' income and Focus Group Discussion (FGD). Analysis of the data using the Index Comparison method, farming margins, and income analysis. The results of the Index Comparative analysis show that strengthening the function of farm management in agricultural development plays a role in increasing farming skills, increasing farmers' work ethic, increasing farm production, and increasing farmers' income. The results of the farming margin analysis show that the average farm production in 2018 is 3.2 tons per hectare a year, an increase in 2020 average production of 5.2 tons per hectare a year. By increasing farming production, the income of Waleale Village farmers in 2018 will increase by an average of IDR 12,020,000. to an average of Rp. 20,743,000 in 2020 or farmers' income increased by an average of 58.82 percent.